2020
DOI: 10.3390/ma13102250
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Strain Path, Texture, Twinning, and Mechanical Properties in Twinning-Induced Plasticity Steel during Wire Drawing

Abstract: The effect of changing the strain path on texture development, twin kinetics, and mechanical properties in twinning-induced plasticity steel was investigated to understand twinning behavior in more detail. Among the various plastic deformation processes, the wire drawing process was selected to achieve the aims of the study. Specimens of cold-drawn TWIP steel wire under the same effective strain but with different crystallographic textures were successfully fabricated using the effect of the wire drawing direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…The texture analysis revealed typical deformation textures for austenitic wire when deformed under uniaxial stress, e.g., via cold-drawing. As reported by Engler et al [45] for face-centered cubic materials with low stacking fault energy in general or by Hwang [46], specifically for austenitic steel wire, cold-drawing leads to the evolution of two fiber textures with the h111i and h100i direction parallel to the drawing direction. The stronger component, which turned out to be the h111i fibre, is documented to have an enhancing effect on the twinning rate [46].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The texture analysis revealed typical deformation textures for austenitic wire when deformed under uniaxial stress, e.g., via cold-drawing. As reported by Engler et al [45] for face-centered cubic materials with low stacking fault energy in general or by Hwang [46], specifically for austenitic steel wire, cold-drawing leads to the evolution of two fiber textures with the h111i and h100i direction parallel to the drawing direction. The stronger component, which turned out to be the h111i fibre, is documented to have an enhancing effect on the twinning rate [46].…”
Section: Discussionmentioning
confidence: 66%
“…As reported by Engler et al [45] for face-centered cubic materials with low stacking fault energy in general or by Hwang [46], specifically for austenitic steel wire, cold-drawing leads to the evolution of two fiber textures with the h111i and h100i direction parallel to the drawing direction. The stronger component, which turned out to be the h111i fibre, is documented to have an enhancing effect on the twinning rate [46]. Comparing the results from texture analysis it can be summarized that the strengthening of the h111i fibre at increasing degrees of cold deformation goes in hand with the enhanced deformation-induced twinning, observed after applying CR of C 48.7%.…”
Section: Discussionmentioning
confidence: 66%
“…The formation of the ω phase always leads to a significant improved strength with a decreased elongation of the titanium alloy [ 30 , 31 ]. The formation of deformation twinning not only induces the strengthening but also has a twinning-induced plasticity (TWIP) effect [ 32 , 33 ]. Therefore, the increase in strength is due to the co-work of deformation twinning and the ω phase.…”
Section: Resultsmentioning
confidence: 99%
“…It was already demonstrated that tailoring recrystallization annealing treatments in TWIP steels can allow to finely tune grain size together with second phase size and shape, which in turn can alter processability and mechanical properties of final products [ 31 , 35 , 36 ]. Thermal treatments can also strongly impact texture evolution, which also affects the final microstructure and processability of TWIP steels into semi-finished products [ 31 , 37 ].…”
Section: Discussionmentioning
confidence: 99%